Pengaruh Pembagian Kerja Terhadap Kepuasan Kerja: Studi Kasus pada Pegawai di Perum DAMRI Bandung - Pratiwi; Tiorida, Ermina (Jurnal Riset Bisnis dan Investasi, 2021)
The background of this research is based on the phenomenon where the placement of employees hasn’t been adjusted to the skills and educational background. In addition, the unequal division of labor causes productivity to decrease, resulting in an attitude of dissatisfaction shown by employees. This study aims to analyze the effect of the division of labor on employee job satisfaction. This study uses a quantitative approach to explanatory survey methods with a sample of 101 respondents who are employees of the Perum DAMRI Bandung office. Data processing was carried out using IBM SPSS Statistics 24. In this study, it was found that the division of labor was in the sufficient category and the job satisfaction was in a good category. The results of this study there’s a positive and significant influence on the division of labor on job satisfaction of Perum DAMRI Bandung employees with an influence value of 24.4%.